Factors Influencing Customer Loyalty in the Indonesian Hotel Industry: The Role of Price Value, Physical Environment, Emotional Experience, and Customer Satisfaction: Factors Influencing Customer Loyalty in the Indonesian Hotel Industry: The Role of Price Value, Physical Environment, Emotional Experience, and Customer Satisfaction - herdianti, Revi Herdianti; Utami, Veronica (Lentera Jurnal Pengabdian Masyarakat, 2026)
This paper investigates how price value, physical environment, emotional experience, and customer satisfaction affect customer loyalty in the Indonesian hotel industry. Growing competition among hotels and the rapid growth in the tourism industry have made customer loyalty an important aspect of maintaining and surviving in the market. The research of this paper used a quantitative method with a cross-sectional approach. The data in this paper was collected using an online questionnaire to 151 respondents who visited hotels in Indonesia in the past 12 months. The data were analyzed using a combination of descriptive analysis, test of validity and reliability, correlation and multiple linear regression using SPSS. The results show that customer experience and satisfaction have a positive impact on loyalty, but price, value and the physical environment do not impact customer loyalty. However, each variable positively impacts customer loyalty when examined together. The model accounts for 56.5% of the variation in customer loyalty, which demonstrates moderate impact. This shows that other variables may help improve customer loyalty. Within the hotel industry, the emotional experience and satisfaction of customers are crucial. So, hotel operators need to develop a strategy that provides a way for customers to participate in positive experiences and high satisfaction levels.